Doggone deadly - Blake, Deborah (Writer of paranormal) (Blake, Deborah (Writer of paranormal). Catskills pet rescue mysteries., 2021)
When her best friend, dog groomer Suzi, is framed for murder at the local dog show, Kari Stuart and her clever kitten Queenie must paw through the clues to catch the real killer.